Breathing And Stretching Exercises Affect The Decrease in The Intensity of Leg Cramp Pain - Achwan Achwan; Abdurahman B.B. Laksono (Jurnal Ilmu dan Teknologi Kesehatan, 2021)
Leg cramps are a common side effect of intradialysis CKD patients. Preventing intradialysis cramping pain can improve quality of life. Breathing and stretching exercises are non-pharmacological treatments for cramping pain. The purpose of this study was to prove the effect of breathing and stretching exercises on changes in the intensity of leg cramps in hemodialysis patients at the Haji Jakarta Hospital in 2018. This study was a quasi-experimental study with a two-group pre-post test research design. The sample was selected by purposive sampling, a sample of 34 patients. The intensity of muscle cramps was measured using the Numeric Rating Scale. The results of the analysis using the paired sample T-test. The results showed that the intervention group had a P-value = 0.01 and the control group had a P-value = 0.055, meaning that there was a difference in mean the intensity of cramping pain before and after breathing and stretching exercises was compared, so it was concluded that there was an effect of breathing and stretching exercises on the intensity of intradialysis leg cramps. Patients are advised to breathing and stretching exercises regularly, light exercise, eat and drink diet.